2014
DOI: 10.1002/btpr.1906
|View full text |Cite
|
Sign up to set email alerts
|

Control of galactosylated glycoforms distribution in cell culture system

Abstract: Cell culture process conditions including media components and bioreactor operation conditions have a profound impact on recombinant protein quality attributes. Considerable changes in the distribution of galactosylated glycoforms (G0F, G1F, and G2F) were observed across multiple CHO derived recombinant proteins in development at Eli Lilly and Company when switching to a new chemically defined (CD) media platform condition. In the new CD platform, significantly lower G0F percentages and higher G1F and G2F were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…These studies have typically demonstrated the desired effect of facilitating an increase or decrease in enzyme activity, which resulted in the targeted manipulation of the final N‐glycan oligosaccharide profile. At the substrate level, selective media supplementation of nucleotide‐sugar precursors, as well as other media supplements have showed a good deal of promise . From the literature reported results, an overall conclusion can be made that protein glycosylation profiles are fairly sensitive toward the enzymes and substrates involved in the metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have typically demonstrated the desired effect of facilitating an increase or decrease in enzyme activity, which resulted in the targeted manipulation of the final N‐glycan oligosaccharide profile. At the substrate level, selective media supplementation of nucleotide‐sugar precursors, as well as other media supplements have showed a good deal of promise . From the literature reported results, an overall conclusion can be made that protein glycosylation profiles are fairly sensitive toward the enzymes and substrates involved in the metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…A change in pH from 6.9 to 7.4 was shown to influence the specific growth and mAb production rates as well as the glycosylation profile of IgG3 produced in hybridoma cells (Müthing et al, 2003). Finally, a multitude of chemical supplements added in either media or feeds have been described in the literature as effective glycosylation modulators and are summarized in detail in Table 1 (Bischoff, Liscum, & Kornfeld, 1986;Bruhlmann et al, 2017;Chang et al, 2007;Chen & Harcum, 2006;Crowell, Grampp, Rogers, Miller, & Scheinman, 2007;Foddy & Hughes, 1988;Gramer et al, 2011;Gramer, Goochee, Chock, Brousseau, & Sliwkowski, 1995;Green, Adelt, Baenziger, Wilson, & Van Halbeek, 1988; Gross et al, 1986;Gu & Wang, 1998;Hollister, Conradt, & Jarvis, 2003;Hossler et al, 2014;Jing, Qian, & Li, 2010;Jones et al, 2004;Kamińska, Dzięciol, & Kościelak, 1999;Keppler, Horstkorte, Pawlita, Schmidt, & Reutter, 2001;Kuntz, Zhong, Guo, Rose, & Boons, 2009;Li, 2014;McCracken, Kowle, & Ouyang, 2014;Mitchelson, Hughes, Mondia, & Hyde-Deruyscher, (2015); Pande, Rahardjo, Livingston, & Mujacic, 2015;Rillahan et al, 2012;Rodriguez, Spearman, Huzel, & Butler, 2005;Slade, Caspary, Nargund, & Huang, 2016;Tropea et al, 1990;Yin et al, 2017;Zhang et al, 2016). Sou et al evaluated the influence of a temperature shift from 36.5 to 32°C in the late exponential phase of a fed-batch experiment on the mAb Fc-glycan profile.…”
mentioning
confidence: 99%
“…In the same study, 20 mM GlcNAc addition effected a 4% decrease of galactosylated entities. In another test, the asparagine concentration influenced the distribution of G0F, G1F and G2F, likely due to altered enzyme activity caused by increased intracellular pH, where higher G0F and lower G1F and G2F emerged with increasing asparagine levels (supplementation of 0-10 mM Asn) 125 .…”
Section: Galactosylationmentioning
confidence: 97%